The Effect of Application Method and Dosage of Manure on Growth and Yield of True Shallot Seed in West Sumatera - Atman Atman; Irfan Suliansyah; Aswaldi Anwar; Syafrimen Yasin (Green Engineering Society, 2022)
To increase shallot productivity, it is necessary to apply true shallot seed (TSS) cultivation technology. This study aimed to determine the suitable method of application and dosage manure in increasing the bulb yield of true shallot seed. The research was conducted at the Experimental Garden of Sukarami AIAT, West Sumatera (altitude 1000 m above sea level and soil type Andosol). The research arranged using a Split Plot Design in randomized blocks, each with 3 replications. Main plot treatment (A) is a application method of manure which consists of 2 types, namely: A1 (given in a spread) and A2 (given in the planting hole). While the treatment of subplots (B) was the dosage of cow manure consisting of 6 types, namely: B1 (0 t/ha), B2 (5 t/ha), B3 (10 t/ha), B4 (15 t/ha), B5 (20 t/ha) and B6 (25 t/ha). The seeds of the Lokananta variety were six weeks after sowing, planted at a spacing of 10x10 cm, 1 seedling/planting hole, on a plot measuring 5x1 m. The results showed that there were highly significant interactions were only found in bulb weight per clump and bulb diameter. The highest dry bulb yield was obtained at a dosage of 15-25 t/ha of manure. In order to make farming activities more efficient, it is recommended to use 15 t/ha of cow manure with the application method by spreading or in planting holes in the cultivation of true shallot seed in West Sumatera.